2003
DOI: 10.1081/jas-120017983
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap Between Doctors' and Patients' Expectations of Asthma Management

Abstract: The Living with Asthma Survey suggests that national asthma management goals are not being achieved in a high proportion of patients, with evidence for both underprescribing and underusage of preventer medication. Achieving closer alignment between medical and patient perspectives is an important goal of asthma education and management in order to help bridge the gap between current concepts of best practice and the reality of persistently poor asthma outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 13 publications
1
41
0
1
Order By: Relevance
“…5 However, it has specific benefits for children with asthma, including reduced hospital admissions, reduced school absenteeism, fewer consultations with GPs, reduced medication, 6 and improved ability to cope with asthma. 7 Despite these benefits, rates of physical activity among young people with asthma are lower than their nonasthmatic peers, [8][9][10][11][12] and are continuing to decline as rates fall more generally among young people in most industrialised nations. 13,14 Three interconnected factors affect participation in physical activity by children with asthma: the illness beliefs of young people; 15,16 parental and family beliefs; 9,17 and the knowledge of teachers and organisational arrangements in schools.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, it has specific benefits for children with asthma, including reduced hospital admissions, reduced school absenteeism, fewer consultations with GPs, reduced medication, 6 and improved ability to cope with asthma. 7 Despite these benefits, rates of physical activity among young people with asthma are lower than their nonasthmatic peers, [8][9][10][11][12] and are continuing to decline as rates fall more generally among young people in most industrialised nations. 13,14 Three interconnected factors affect participation in physical activity by children with asthma: the illness beliefs of young people; 15,16 parental and family beliefs; 9,17 and the knowledge of teachers and organisational arrangements in schools.…”
Section: Introductionmentioning
confidence: 99%
“…GINA guidelines state that ''it is reasonable to expect that in most patients with asthma, control of the disease can and should be maintained.'' However, despite the availability of guidelines, a substantial proportion of adults as well as children with asthma is not optimally controlled [6][7][8][9][10].…”
mentioning
confidence: 99%
“…35 In the Living with Asthma Study performed in Australia, one in five children with asthma did not ride a bike, play at school or play with animals, and one in three did not participate in organised sports. 36 The study also reported that parents of children with asthma were more anxious than parents of children who did not have asthma. In a UK study of children with asthma aged between 5 and 17 years, children reported that asthma restricted their participation in everyday activities and caused frequent school absences and night disturbances.…”
Section: Impact Of Asthma On Health-related Quality Of Life In Childrenmentioning
confidence: 82%